(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2023)
Both of the prevalence and development of electronic learning lead to the necessity of the availability of the related skills to this type of learning which in turn enables the teaching staff member to be operative and to make full use of the system. Based on that, the study aims at acquiring the availability or not of these adequacies or sufficiency in electronic learning that should be seized by the staff members of the technical institute/ Nineveh “based on their own perspective”. This sufficiency is metered through the following adequacies: Having the computer using adequacy, networks using adequacy, designing and managing e-learning adequacy, electronic knowledge adequacy. The study used the descriptive analytic approach in processing the collected data which is a sample of “37” members of the teaching staff of the institute. The procedure was to fill a questionnaire disseminated to them through a link over google drive which is “https://forms.gle/D7GiLasZTs2paEV68”. In addition, the programming statistic aid “SPSS V.25” has been used in analysing data. The study came up with some conclusions, most importantly was the proven availability of the learning adequacies needed for the teaching staff and the varying percentage over the availability of these four adequacies within the teaching staff. The study proposed that it is a must to overcome the limitations over using up to date technologies by the teaching staff alongside with enhancing financial and human resources for better enactment of electronic learning at the institute.